Legal Culture Terhadap Partisipasi Masyarakat dalam Pelaporan Pelanggaran Pemilu di Kota Makassar - Lenni Lenni; Muhammad Na'afil Kamal Putra; Leni Hardiani; Ira Febrianti; Insyirah Fatihah Hidayat; Muhammad Zulfan Hakim (LPPM Universitas Ekasakti Padang, 2023)
One form of democracy in monitoring general elections by the public is by reporting election violations. Election violations from 2014 to 2019 increased by 151.3% and the discovery of violations was dominated by Bawaslu findings rather than public reporting. In the case of a decrease in reporting by the public, an analysis of legal culture, namely knowledge, awareness, and attitudes of the public, is carried out to find the factors causing the decrease in reporting. Quantitative and qualitative approaches were used in the form of questionnaires and interviews. Furthermore, a causal relationship was found between legal culture, legal substance, and legal structure so efforts are needed to improve the quality of legal substance, legal structure, and legal culture of the society to increase public participation in the 2024 General Election.